2017
DOI: 10.1002/jcb.26131
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A Suppresses Specificity Protein 1 as a Novel Target in Human Breast Cancer Cells

Abstract: Licochalcone A (LCA), isolated from the root of Glycyrrhiza inflata, are known to have medicinal effect such as anti-oxidant, anti-bacterial, anti-viral, and anti-cancer. Though, as a pharmacological mechanism regulator, anti-cancer studies on LCA were not investigated in human breast cancer. We investigated the anti-proliferative and apoptotic effect of LCA in human breast cancer cells MCF-7 and MDA-MB-231 through MTS assay, PI staining, Annexin-V/7-AAD assay, mitochondrial membrane potential assay, multi-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…The structure of licochalcone A and various biological activities have been established to date (Figure 1) (10), including anti-inflammatory (11), anti-oxidation (12), antiseptic, and anti-tumor properties (13, 14). As a traditional Chinese medicine monomer with anti-inflammatory and anti-bacterial properties (15, 16), it has several advantages over traditional antibiotics. Drug resistance to this compound is relatively uncommon (17), along with a significant inhibitory effect on inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of licochalcone A and various biological activities have been established to date (Figure 1) (10), including anti-inflammatory (11), anti-oxidation (12), antiseptic, and anti-tumor properties (13, 14). As a traditional Chinese medicine monomer with anti-inflammatory and anti-bacterial properties (15, 16), it has several advantages over traditional antibiotics. Drug resistance to this compound is relatively uncommon (17), along with a significant inhibitory effect on inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that LA induces apoptosis in glioma cells, lung cancer cells, and gastric cancer cells [21,22,23,24]. LA has also been found to increase autophagy and arrest the cell cycle in breast cancer cells [25,26], and induce apoptosis via the suppression of specificity protein 1 in breast cancer cells [27]. However, the mechanism underlying the modulated invasion and migration of breast cancer cells by LA is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Licochalcone A caused apoptosis of BGC human gastric cancer cells (Khazraei‐Moradian et al, ). Licochalcone A and glabridin showed antiproliferative and apoptotic effects in human breast cancer cells MCF‐7 and MDA‐MB‐231 and attenuated tumor growth, mesenchymal characteristics, and cancer stem cell‐like properties (Jiang et al, ; Kang et al, ).…”
Section: Discussionmentioning
confidence: 99%